Effects of Exercise Interventions on Peripheral Brain-Derived Neurotrophic Factor: An Umbrella Meta-Analysis Across Clinical and Healthy Populations - Mesut Süleymanoğulları; Cemre Didem Eyipınar; Raul Ioan Muntean; Halil İbrahim Ceylan (Journal of Clinical Medicine, 2026)
Background and Objectives: Brain-derived neurotrophic factor (BDNF) supports neuronal function and plasticity, but exercise meta-analyses may reuse primary studies and combine distinct outcomes. We evaluated review-level evidence while preventing direct reuse of the same primary-study evidence within pooled syntheses in this umbrella review and meta-analysis. Methods: Thirty-nine systematic reviews with quantitative syntheses of peripheral BDNF were assessed. Review–primary-study links were normalized, methodological quality was appraised with AMSTAR 2, and estimates were classified by exercise timing and comparison design. Only reviews meeting the zero-overlap criterion were pooled using restricted maximum likelihood random-effects models with Hartung–Knapp inference. Prediction intervals were calculated; network and dose–response findings were summarized separately. Results: The corpus included 507 review–primary-study occurrences representing 289 unique normalized primary-study identities (corrected covered area [CCA], 1.99%). AMSTAR 2 overall confidence was low in eight reviews and critically low in 31. Seven reviews meeting the zero-overlap criterion contributed to the chronic-controlled synthesis, yielding a pooled SMD of 0.85 (95% CI 0.07–1.64; I2 = 93.9%; 95% prediction interval −1.20 to 2.91). Acute-controlled effects were inconclusive (four reviews; SMD 0.49, 95% CI −0.07 to 1.05; I2 = 53.8%), as were chronic pre–post effects (three reviews; SMD 0.32, 95% CI −0.04 to 0.69; I2≈0%). Quality-restricted meta-analysis was not estimable, and small-study-effect tests were not performed because no synthesis set contained at least 10 independent reviews. Conclusions: Exercise may increase peripheral BDNF in some chronic-controlled settings, but effects vary substantially. Circulating BDNF does not directly establish central BDNF engagement or enhanced neuroplasticity, and current review-level evidence does not establish a universal response, clinical benefit, superior modality, or optimal dose.